Aggregated associations – The method, algorithm, uses - Šarmanová, Jana; Takács, Ondřej; Oujezdský, Aleš (AIP conference proceedings, 2017)
The classical method of finding associations in the data matrix with the given support and reliability may not lead to finding all relevant facts in the data. This paper deals with a modified method of searching for so called aggregated associations, which can also find other non-trivial facts. The paper describes an algorithm that finds hypotheses of the form of aggregated associations and demonstrates its use in a practical example.